SISTEM AKUNTANSI PENJUALAN KREDIT DAN PENAGIHAN PIUTANG PADA PT.KEDAUNG INDUSTRIAL GROUP BATAM - Ria Afryani; Hendry Jaya; Rizki Eka Putra (Universitas Riau Kepulauan, 2015)
Credit Sales Accounting System and Account Receivable Collection at PT.Kedaung Industrial Group Batam. Guided by Mr. SYAHRIL EFFENDI, SE,M.Ak and Mr.HENDRY JAYA, SEEshtabilished company to search for maximum profit and for the maintinly the viability of their business. Absolutely the business continuity can be realized it the goods or service acceptable in the market and get consumen interesting. There for something important to company’s learn about sale system. Because, sale is resource one of the way that used sale increasing is with credit sale system.This research is intended to know about Credit Sales Accounting System and Account Receivable Collection. Do research on one of these distributor glassware, mainly PT.Kedaung Industrial Group cab Batam. Located in the area Sekupang Industry kav.57-58 Batam.In doing this research, writer just using the descriptive method. To collect data obtained, interpretation, also analize and then explanation to know problems and get the arguments, researchers obtained data via observation interview.In this paper the author discusses how the accounting system of credit sales and collection of accounts receivable that the company used to compare the events with existing theories. This study was done to avoid fraud on credit sales and collection of accounts receivable.